An objective test to assess upper limb functionality in patients with breast cancer-related lymphedema: investigation of the psychometric properties of the upper limb functional test (ULIFT) - Sukriye Cansu Gultekin; Ahmet Burak Cakir; Zeynep Gulsum Guc; Faruk Recep Ozalp; Merve Keskinkilic; Tugba Yavuzsen; Didem Karadibak (BMC Women's Health)
Abstract Background Although upper limb (UL) functionality was reported to be adversely affected in patients with breast cancer- related lymphedema (BCRL), there is currently no validated, objective performance-based assessment tool designed to evaluate UL function in this population. The Upper Limb Functional Test (ULIFT) was adapted from the ADL test (TGlittre), which is widely used in clinical settings and research, and was developed to assess unilateral UL functionality. Therefore, the present study aimed to evaluate the psychometric properties of the ULIFT in patients with BCRL. Methods The study involved 36 women with unilateral BCRL and 30 healthy women controls. Intraclass correlation coefficients (ICC) were used to assess test-retest reliability. ULIFT was conducted a second time with 36 patients (100% of the total sample) over a period of 7 to 14 days for test-retest reliability analysis. The following measures were used to investigate ULIFT convergent validity: Range of motion was assessed using a universal goniometer; UL disability with the Disability of the Arm, Shoulder and Hand (DASH) questionnaire; hand grip strength with a Jamar dynamometer; and quality of life (QoL) with the Short Form 36-item Health Survey (SF-36) survey, and Upper Limb Lymphedema 27 (ULL-27). The receiver operating characteristic (ROC) curve analysis was conducted as part of the known-group validity assessment to establish a cut-off point for ULIFT in distinguishing between patients with BCRL and healthy controls. Results The ULIFT showed excellent test-retest reliability [ICC [95%] 0.92 (0.86–0.96)], a standard error of measurement of 3.91 s, and a minimum detectable change of 10.83 s. The sensitivity of 72.2%, specificity of 73.3% and AUC of 0.773 indicate a moderate ability of ULIFT to discriminate patients with and without impairment at a cut-off of 110.125 s. Significant correlations were found between ULIFT and UL functional measures (r ≥ 0.3), indicating convergent validity. Conclusion ULIFT is a reliable and valid objective measurement tool for assessing unilateral UL function. The cut-off time of 110.125 s may help in clinical decision-making, particularly when used in conjunction with other assessments.